Measuring Brand Emotional in Increasing Brand Loyalty - Anita Yuliana; Asep Muhamad Ramdan; Acep Samsudin (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Brand loyalty has an important role in advancing a product so that consumers remain loyal in choosing the product that is being marketed. The research aims to determine the effect of brand emotion on brand loyalty. The data analysis technique used is simple linear regression analysis and using non-probability sampling techniques. The data was collected by distributing questionnaires using Google Form and 130 respondents were used in the city of Sukabumi. This research data processing using IBM SPSS version 24 software. The results of this research indicate simultaneously and partially that brand emotion has a positive influence on brand loyalty. The results of the f-test, namely from the value of count fount 309.253> 3.07 show that count is greater than the table and the correlation results in this study have a very high value, namely 0.841.